The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0231874
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the age-period-cohort effects on the temporal trend mortality from schistosomiasis in Brazil from 1980 to 2014

Abstract: Background Schistosomiasis is highly debilitating and related to poverty, leading to chronic health problems. This disease is important for public health due to the high prevalence, severity of clinical forms and heterogeneous spatial and temporal patterns. In Brazil, about 1.5 million people are at risk of infection with Schistosoma mansoni, with an annual average of 500 deaths. In this study, the temporal change in mortality was evaluated in relation to the effects of age, period and birth cohort, in Brazil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
2
9
0
4
Order By: Relevance
“…Different mortality rates in males, as well as the higher prevalence of the disease in this group, justify the importance of specific actions for this population, as indicated in previous publications [19][20][21] . However, the labor market and the greater prominence of women also generate occupational risks for women, which may cause changes in the mortality patterns in the future 19 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Different mortality rates in males, as well as the higher prevalence of the disease in this group, justify the importance of specific actions for this population, as indicated in previous publications [19][20][21] . However, the labor market and the greater prominence of women also generate occupational risks for women, which may cause changes in the mortality patterns in the future 19 .…”
Section: Discussionmentioning
confidence: 70%
“…It is possible that some of these children migrated to other regions of Brazil or to urban areas of the same state or municipality, where they had no contact with S. mansoni. In contrast, those who persisted in areas of higher endemicity may have reinfected themselves and were more likely to develop more severe clinical forms, with potential progression to death 21,22 . This may also explain the maintenance of higher mortality rates in older people.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, com as ações do Programa de Controle da Esquistossomose (PCE), implantado na década de 1980, os índices de gravidade reduziram. Somado a isso, o avanço no conhecimento sobre a história natural da doença e a ampliação dos serviços de saúde, com diagnóstico e tratamento, acarretaram a redução da mortalidade e o aumento da sobrevida dos indivíduos infectados 7 . Contudo, a transmissão da doença é observada em 19 dos 27 estados, sendo considerado o país mais afetado pela esquistossomose nas Américas, com 42,9 milhões de pessoas sujeitas ao risco de infecção e aproximadamente 1,5 milhão de indivíduos infectados [8][9][10] .…”
Section: Introductionunclassified
“…In Brazil, by virtue of the activities of the Schistosomiasis Control Program (PCE), there has been a significant reduction in schistosomiasis severity indicators in recent decades [ 3 ]. Additionally, the improvements in health service strategies, as diagnosis and mass treatment in endemic areas, have dropped the number of cases and deaths and increased life expectancy for ill patients [ 3 ]. Regardless all these measures, schistosomiasis remains endemic in many states, mainly in the Northeast region [ 4 , 5 ].…”
mentioning
confidence: 99%
“…Furthermore, prior studies conducted by our group showed an increase in the schistosomiasis mortality rate in age groups above 60 years [ 4 , 6 ]. Thereby, it suggests the chronicity of the disease, a higher risk of association with comorbidities, and death [ 3 , 7 ].…”
mentioning
confidence: 99%